Quality in Legal Translation - Hendrik J. Kockaert; Nadia Rahab (JoSTrans: The Journal of Specialised Translation)
This article introduces a special issue on quality in legal translation. It situates legal translation in today's context in the landscape of professional translation and Translation Studies and this issue as primarily inspired by the European project, Qualetra which focuses on translation procedural rights in criminal proceedings. The article then proceeds to describe the project before proposing an overview of the contributions to this issue.